A multiple regression analysis of syntactic and semantic influences in reading normal text - Joel Pynte; Boris New; Alan Kennedy (Bern Open Publishing, 2008)
Semantic and syntactic influences during reading normal text were examined in a series of multiple regression analyses conducted on a large-scale corpus of eyemovement data. Two measures of contextual constraints, based on the syntactic descriptions provided by Abeillé, Clément et Toussenel (2003) and one measure on semantic constraint, based on Latent Semantic Analysis, were included in the regression equation, together with a set of properties (length, frequency, etc.), known to affect inspection times. Both syntactic and semantic constraints were found to exert a significant influence, with less time spent inspecting highly constrained target words, relative to weakly constrained ones. Semantic and syntactic properties apparently exerted their influence independently from each other, as suggested by the lack of interaction.